The Prospective Assessment of Nutrition in Children with Cystic Fibrosis - Moeeni, Vesal; Shojaee, Pardis; Kianifar, Hamidreza; Walls, Tony; Pattemore, Philip; Day, Andrew S. (International Journal of Child Health and Nutrition, 2015)
Aims: Patients with Cystic Fibrosis (CF) have increased risk of malnutrition. Early detection of nutritional deterioration enables prompt intervention and correction. The aims of this project were to define the nutritional status of CF patients in Iran and New Zealand, compare and contrast the McDonald Nutritional Risk Screening (NRS) tool with the Australasian Guidelines for Nutrition in Cystic Fibrosis, and validate these results with each patient’s evaluation by their CF clinical team. Methods: Children with CF (2 - 18 years) were assessed during routine outpatient visits over one year. Anthropometric measurements were obtained. Both tools were applied and the results compared to their clinical evaluation (as gold standard) with calculation of specificity and sensitivity. Results: Under-nutrition was seen more frequent in the 33 Iranian children than in the 36 New Zealand (NZ) patients (39% versus 0%, p=0.0001), whereas over-nutrition was more prevalent in NZ children (9% versus 17%, p=0.05). At the first visit, both guidelines were able to recognize 77% and 61% of under-nourished Iranian patients, respectively. The mean sensitivity and specificity for all visits for the McDonald tool were 83% & 73% (Iran) and 65% & 86% (NZ). Sensitivity and specificity for the Australasian guidelines were 79% & 79% (Iran) and 70% & 90% (NZ). Conclusions: Both tools successfully recognised patients at risk of malnutrition. The McDonald tool had comparable sensitivity and specificity to that described previously, especially in Iranian patients. This tool may be helpful in recognizing at risk CF patients, particularlyin developing countries with fewer resources.